PERENCANAAN KEBUTUHAN BAHAN BAKU SERTA PENGENDALIAN PERSEDIAAN BAHAN BAKU INDUSTRI PENGOLAHAN TEMPE KEDELAI (STUDI KASUS : UMKM TEMPE KEDELAI â€œMURNIâ€ MADIUN) - Indrawati, Chatarina Dian (Widya Warta, 2016)
The UMKM’s of soybean processing in Madiun is 100 in number. All of them are small home industries Most of the soybean processing businesses do not make use of good management system yet. Consequently, they face so many problems and barriers to develop their businesses. One effort in the management system intended is concerned with supply control and determination of daily production, which will influence the operation of those companies. It is due to the fact that the two aspects are closely related to the level of market demand. If the amount of production and the number of requests are not met or approached at a point, then there will be a loss. In Murni, one of the UMKM’s of soybean processing, it frequently happens that the number of production is excessive or short compared to the market demand in the period of production. As a result, some of the soybean is not saleable, or market demand is not met. The data analysis indicates that the total need for raw materials of soybean per year is 85,403 kg. In connection with stock planning, the analysis using POQ method shows that reservation interval (T) is 4 periods ahead and requires a total cost of IDR 617,449,375 annually.